Meaning of social and cultural factors in cognitive development - Dongo M., Adrián (2009)
The problem of studying social and cultural factors which take part in the cognition development is related to the global and unilateral treatment of those factors in relation to the individual ones. Specifically, the problem appears when we do not differ the interindividual social factors action from the social factors of cultural transmission. In the present study, we will analyze the action of social and cultural factors in the development of knowledge structures, aiming at showing its differentiated and complementary actions. As a result of this objective, in the first place we will analyze the characteristics and complementary actions of the development factors in general (individual and social ones). Secondly, we will analyze researches accomplished in different social and cultural environments which make its differentiated and complementary actions evident. Finally, we will try to make evident the novelty and importance of the relational treatment of social and cultural factors for the basic and applied research.